Pharmacovigilance: Knowledge, Attitude and Practice among Medical Professionals at a Tertiary Care Hospital in Nepal - Kamal Kandel; Naresh Karki; Kyushu Shah; Pravin Prasad (Journal of Lumbini Medical College, 2021)
Introduction: Awareness regarding pharmacovigilance and adverse drug reaction reporting by medical professionals significantly contribute to the safer use of medicine. Therefore, the objective of this study was to assess the knowledge, attitude, and practices regarding pharmacovigilance among the medical professionals at a tertiary care hospital in Nepal. Methods: This study was a descriptive cross-sectional study conducted at Lumbini Medical College and Teaching Hospital. Printed questionnaires were distributed to all the medical professionals and collected data were analyzed to find the knowledge, attitude, and practices of the medical professionals regarding pharmacovigilance. Results: A total of 107 medical professionals, 77 (71.96%) males and 30 (28.04%) females, participated in the study. The overall response rate was 98.16%. In this study,70.1% of medical professionals knew the definition of pharmacovigilance, and more than half of the participants(63.6%) did not know the existence of the national pharmacovigilance center. Regarding attitude, 52.3% of the medical professionals strongly agreed that adverse drug reaction reporting and monitoring systems were beneficial to patients or improved patient care. Half of the medical professionals would sometimes counsel the patients about adverse drug reactions. Almost half of  medical professionals mentioned that the major factor behind underreporting was insufficient knowledge of where to report adverse drug reactions. Training on pharmacovigilance was the main recommendation from the participants (52.3%) to improve the pharmacovigilance program. Conclusion: There is room for improvement in the knowledge, attitude and practice of the participants. Most medical professionals suggested training or continuing medical education as a way to improve pharmacovigilance programs.